OPTIMASI KEUNTUNGAN PENJUALAN DAGING PADA PT HIJRAH FOOD MENGGUNAKAN PEMROGRAMAN LINEAR - Agung Listianto; Muhammad Farikh Hidayat Julio, Muhamad Fadillah, Rendy Rusdiyanto, Paduloh (Jurnal Ekonomi dan Bisnis, 2025)
This study aims to optimize the profit of meat sales at PT Hijrahfood through the application of linear programming method. Since its establishment in 1992, PT Hijrahfood as a meat distributor has faced significant challenges in increasing profitability amid increasingly fierce competition. With the increasing demand for quality meat products, the company needs to design effective strategies in managing production and sales. In this study, we developed a mathematical model to analyze the relationship between various variables that affect profits, such as production costs and selling prices. The graphical method is used to visualize the objective function as well as the constraints, enabling the discovery of the optimal solution. It is hoped that the results of this study can provide in- depth insight into better management strategies, as well as improve the efficiency and profitability of PT Hijrahfood. Thus, this research is not only relevant for PT Hijrahfood, but is also expected to make a meaningful contribution to the meat distribution industry as a whole.